Employing bureaucracy : managers, unions, and the transformation of work in the 20th century - Jacoby, Sanford M., 1953- (Organization and management series (Routledge (Firm)), 2004)
This revised edition of "Employing Bureaucracy" is an attempt to understand how industrial labour was transformed and to identify the historical process by which good jobs were created. It is, therefore, an account of the bureacratization of employment.